A Key, Not a Straitjacket: The Case for Interim Mental Health Legislation Pending Complete Prohibition of Psychiatric Coercion in Accordance with the Convention on the Rights of Persons with Disabilities - Laura Davidson (Harvard FXB Center for Health and Human Rights, 2020)
The practice of coercion on the basis of psychosocial disability is plainly discriminatory. This has resulted in a demand from the Committee on the Rights of Persons with Disabilities (the CRPD Committee) for a paradigm shift away from the traditional biomedical model and a global ban on compulsion in the psychiatric context. However, that has not occurred. This paper considers conflicting pronouncements of the CRPD Committee and other United Nations bodies. Assuming the former's interpretations of the Convention on the Rights of Persons with Disability (CRPD) are accurate, involuntary psychiatric detention and enforced treatment on the basis of psychosocial disability are prima facie discriminatory and unlawful practices. However, dedicated mental health legislation both permits discrimination and protects and enhances rights. This paper proposes a practical way out of the present impasse: the global introduction of interim "holding" legislation lacking full compliance with the CRPD. While imperfect, such a framework would facilitate a move toward a complete ban on psychiatric coercion. The paper outlines four essential ingredients that any interim legislation ought to contain, including clear timebound targets for full CRPD implementation. It concludes by urging the CRPD Committee to take the unprecedented step of issuing a general comment providing reluctant "permission" for the progressive realization of respect for articles 12 and 14 of the CRPD.